2023
DOI: 10.1097/dcr.0000000000002651
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Definitions and Interpretation Templates for Dynamic Ultrasound Imaging of Defecatory Pelvic Floor Disorders: Proceedings of the Consensus Meeting of the Pelvic Floor Disorders Consortium of the American Society of Colon and Rectal Surgeons, the Society of Abdominal Radiology, the International Continence Society, the American Urogynecologic Society, the International Urogynecological Association, and the Society of Gynecologic Surgeons

Abstract: The articles are identical except for minor stylistic and spelling differences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Research has shown adequate accuracy of integrated total pelvic floor ultrasound to both clinical findings and defaecatory imaging especially in the evaluation of obstructive defaecation [14]. The cost effective, easy to use modality can also be used to evaluate the results of treatment in an outpatient setting which can help navigate management plans.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown adequate accuracy of integrated total pelvic floor ultrasound to both clinical findings and defaecatory imaging especially in the evaluation of obstructive defaecation [14]. The cost effective, easy to use modality can also be used to evaluate the results of treatment in an outpatient setting which can help navigate management plans.…”
Section: Discussionmentioning
confidence: 99%
“…9 The PFD Consortium attempts to standardize the language in the field of PFUS and to create a universal set of recommendations for a minimum common language for interpretation and reporting of defecatory disorders, with relevance across disciplines and across all PFUS modalities. 7 This standardization is fundamental to reducing the variability in how different physicians and specialties interpret and use findings seen on PFUS, thus making effective communication and cooperation between subspecialties less challenging. Dynamic PFUS can demonstrate a variety of findings, including increased perineal descent, rectoceles, rectal intussusception and prolapse, enterocele, PF dyssynergia, or paradoxical contraction of the puborectalis.…”
mentioning
confidence: 99%
“…6 The power of the collaborative approach is on full display in the Proceedings of the Consensus meeting of the PF disorders Consortium, which achieved consensus on the definitions and interpretation templates for dynamic US imaging of defecatory disorders. 7 Obstructed defecation syndrome (ODS) is difficulty in evacuating stools, requiring straining efforts at defecation, having the sensation of incomplete evacuation, or needing to manually assist defecation. 8 This is due to a physical blockage of the fecal stream during defecation attempts caused by several morphological or functional conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation